Dampak Psikologis dan Upaya Penanggulangan Kekerasan Seksual Terhadap Perempuan - Anindya, Astri; Syafira, Yuni Indah; Oentari, Zahida Dwi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
Cases of violence against women often occur, for example sexual violence that arises in the community because of a lack of community understanding of acts of violence in the surrounding environtment, economic factors, wrong relationships and infidelities that occur in the house hold. This research was conducted because it has the purpose of the impact of violence against woman Qualitative research is used in orde to be descriptive and conditional and analysis. And using a data accumulation system wit a library that is a way to accumulate data from books, online media or other sources, so the research data is taken using secondary data. So that research data is not taken directly from the source or respondent. Data analysis techniques utilize documents as research data by analyzing the contents of documents in order to find characteristics and draw conclusions. The results of the psychological impact of sexual violence caused the victim to become traumatized and depressed, resulting in victims of sexual violence feeling ostracized and wanting to avoid the circumstances they experienced. Then the efforts undertaken as a form of overcoming the psychological impact of sexual violence on women include developing a sense of environmental awareness, responsibility for themselves, moral education, and supervision. Whatever the efforts of the government that is rehabilitating victims of sexual violence, operations and raids in places where crime is often committed, provide insight to schools and surrounding communities. With these efforts can prevent violence against women.